2013
DOI: 10.1371/journal.pone.0072820
|View full text |Cite
|
Sign up to set email alerts
|

RECQL1 DNA Repair Helicase: A Potential Therapeutic Target and a Proliferative Marker against Ovarian Cancer

Abstract: ObjectiveThis study analyzed the clinicopathological correlation between ovarian cancer (OC) and RECQL1 DNA helicase to assess its therapeutic potential.MethodsSurgically resected OC from 118 retrospective cases, for which paraffin blocks and all clinical data were complete, were used in this study. RECQL1 and Ki-67 immunostaining were performed on sections to correlate RECQL1 staining with subtype and patient survival. Ten OC and two normal cell lines were then examined for RECQL1 expression and were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…Their results suggested that even in unchallenged cancer cells, RECQL1 serves to promote expression of genes that play important roles in cell migration, invasion and metastasis. These results are in line with a previous observation that RECQL1 expression is up-regulated in cancer cell lines compared to normal cells [89], and elevated in certain types of cancers [9092]. Genes down-regulated upon RECQL1 silencing displayed an enrichment of predicted G4-forming sequences in their promoter elements [88].…”
Section: Human Recq Helicases and Their Roles In Response To Nuclear supporting
confidence: 90%
“…Their results suggested that even in unchallenged cancer cells, RECQL1 serves to promote expression of genes that play important roles in cell migration, invasion and metastasis. These results are in line with a previous observation that RECQL1 expression is up-regulated in cancer cell lines compared to normal cells [89], and elevated in certain types of cancers [9092]. Genes down-regulated upon RECQL1 silencing displayed an enrichment of predicted G4-forming sequences in their promoter elements [88].…”
Section: Human Recq Helicases and Their Roles In Response To Nuclear supporting
confidence: 90%
“…On the other hand, established tumours may be dependent on RECQL1 to tolerate replication induced DNA damage, a feature seen in proliferating cancer cells. In fact RECQL1 has been shown to be overexpressed in glioblastoma (31), hepatocellular carcinoma (32), ovarian cancers (33), melanoma (34) and head & neck cancer models (35). Whether RECQL1 also impacts sporadic breast cancer pathogenesis is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…RECQ1 is overexpressed or amplified in rapidly dividing cancer cells (16, 25, 26) and in human cancer tissues (18, 27, 28). RECQ1 knockdown in cancer cells significantly reduces cell migration and invasion (29), and gene expression analysis has shown that RECQ1 actually regulates genes associated with cancer progression (30).…”
Section: Discussionmentioning
confidence: 99%